Listy do mojego Wuja. Listy Tymoteusza Karpowicza do brata Jana Brzezińskiego - Szkudlarek, Ewa (Przestrzenie Teorii, 2007)
Listy do mojego Wuja. Listy Tymoteusza Karpowicza do brata Jana Brzezińskiego